2012
DOI: 10.1245/s10434-012-2416-1
|View full text |Cite
|
Sign up to set email alerts
|

Is Serum Alpha-Fetoprotein Useful for Predicting Recurrence and Mortality Specific to Hepatocellular Carcinoma After Hepatectomy? A Test Based on Propensity Scores and Competing Risks Analysis

Abstract: Preoperative AFP levels are not useful for predicting recurrence or survival endpoints following curative hepatectomy for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…WASL, which belongs to WASP family, was found to be expressed in colorectal cancer liver metastases and esophageal squamous cell carcinoma [32-34]. WASL and WAVE-2 expression were shown to be extensive in HCC [35]. Researchers try to regulate the expression of WASP family proteins to inhibit the invasion of cancer cells [36-38].…”
Section: Discussionmentioning
confidence: 99%
“…WASL, which belongs to WASP family, was found to be expressed in colorectal cancer liver metastases and esophageal squamous cell carcinoma [32-34]. WASL and WAVE-2 expression were shown to be extensive in HCC [35]. Researchers try to regulate the expression of WASP family proteins to inhibit the invasion of cancer cells [36-38].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst these factors, AFP is the most widely examined biomarker and has been reported to be a potent independent prognostic factor, especially in advanced HCC [27]. However, recent studies have shown that AFP monitoring lacks adequate sensitivity and specificity for effective surveillance and diagnosis and does not have any prognostic significance [28,29,30,31]. In fact, the current guidelines for the management of HCC state that none of the currently existing serological tests can be recommended to survey the patients at risk of developing HCC and that surveillance must be based on an ultrasound examination [15,32].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested using AFP as an indicator to predict clinical outcomes in HCC [32,33]. However, other studies have suggested that serum AFP is not an effective predictor of prognosis in HCC [34][35][36]. In this report, 400 ng/mL was used as the cut-off value to define lower and higher levels of AFP, and we found that a higher AFP level (> 400ng/mL) was significantly associated with shorter (within 2 years) OS and RFS, but not with long-term clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%